Review on some indigenous herbals for neuroprotective effect (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Neurodegeneration refers to a condition of neuronal death occurring as a result of progressive disease of long-term and is becoming a major health problem in the 21st century. Neurons degenerated are not replaced resulting in a cognitive loss, many neurodegenerative disorders, such as schizophrenia, depression, Alzheimer's disease (AD), dementia, cerebrovascular impairment, seizure disorders, head injury, parkinsonism. AMP-activated protein kinase (AMPK) boosts SIRT activation by increasing cellular NAD+ levels, which leads to deacetylation and regulation of downstream SIRT1 targets including peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC-1) (16), a master regulator of mitochondrial biogenesis Thus the herbal plants can be a valuable source of the drug against neurodegenerative disorders which will require high-throughput screening. Glutamate receptor-mediated excitotoxicity has been associated with several diseases of the brain, whereas in vivo and in vitro studies have shown that blocking the NMDA and the non-NMDA receptors simultaneously results in maximum protection against ischemic neurodegeneration. This review will highlight the role of herbal plants and their phytoconstituents against neurodegenerative diseases and other related disorders, focusing on their mechanism of action and therapeutic potential.